Diet, Microbiota and Gut-Lung Connection - Anand, Swadha; Mande, Sharmila S. (Frontiers in Microbiology, 2018)
Microbial community in the gut (Gut microbiome) is known to impact metabolic functions as well as immune response in our body. Diet plays an important role in determining the composition of gut microbiome. Gut microbes help in assimilating dietary nutrients which are indigestible by humans. The metabolites produced by them not only modulate gastro-intestinal immunity, but also impact distal organs like lung and brain. Micro-aspiration of gut bacteria or movement of sensitized immune cells through lymph or bloodstream can also influence immune response of other organs. Dysbiosis in gut microbiome has been implicated in several lung diseases, including allergy, asthma and cystic fibrosis. The bi-directional cross-talk between gut and lung (termed Gut-Lung axis) is best exemplified by intestinal disturbances observed in lung diseases. Some of the existing probiotics show beneficial effects on lung health. A deeper understanding of gut microbiome and its role in respiratory disorders is likely to help in designing appropriate probiotic cocktails for therapeutic applications.